1985
DOI: 10.1080/03079458508436243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the enzyme‐linked immunosorbent assay (elisa), haemagglutination inhibition test and agar gel precipitation test for detection of antibodies to avian infectious bronchitis virus

Abstract: The immune response after vaccination with infectious bronchitis virus (IBV) under field conditions was measured by the ELISA, haemagglutination-inhibition (HI) and agar-gel precipitin (AGP), tests. Vaccinations were performed in three flocks and one experimental group via the drinking water with the vaccine strains H 120 and H 52. In each flock 40 random serum samples were taken every 2 weeks and tested individually. In the experimental group blood samples were collected every week from each of the 10 chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…Reports of indirect ELISAs show them to be group specific (Garcia & Bankowski, 1981;Marquardt et al, 1981;Zellen & Thorsen, 1987;Perrotta et al, 1988;Karaca et al, 1990;De Wit et al, 1997). Antibodies can first be detected by ELISA within 1 week after vaccination or infection (Marquardt et al, 1981;Mockett & Darbyshire, 1981;Hawkes et al, 1983;Monreal et al, 1985;De Wit et al, 1997, 1998a. This early detection does not automatically lead to a high sensitivit y.…”
Section: Group-specific Testsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reports of indirect ELISAs show them to be group specific (Garcia & Bankowski, 1981;Marquardt et al, 1981;Zellen & Thorsen, 1987;Perrotta et al, 1988;Karaca et al, 1990;De Wit et al, 1997). Antibodies can first be detected by ELISA within 1 week after vaccination or infection (Marquardt et al, 1981;Mockett & Darbyshire, 1981;Hawkes et al, 1983;Monreal et al, 1985;De Wit et al, 1997, 1998a. This early detection does not automatically lead to a high sensitivit y.…”
Section: Group-specific Testsmentioning
confidence: 99%
“…The reverse was also true. Monreal et al (1985), Box et al (1988) andDe Wit et al (1997) also reported that the HI test using M41 antigen was not able to detect a primary H120 vaccination, but none of these reports consider whether using Holland antigen would improve detection. This demonstrates that virus strain selection for IBV HI antigen production is important, for sensitivity of the test as well as for interpretation of the results.…”
Section: Haemagglutination Inhibition Testmentioning
confidence: 99%
See 3 more Smart Citations